KOMPETENSI PUSTAKAWAN PERPUSTAKAAN PERGURUAN TINGGI SWASTA (BERBASIS SKKNI) DALAM EKOSISTEM DIGITAL - Agus Utomo; Ipung Sri Purwanti Hery (Central Library of Universitas Sebelas Maret, 2021)
The high access to a digital information, requires librarians to innovate, improve competence in the field of technology and work efficiently in order to facilitate the service of exchanging data, communication and uniformity of information. This Librarian Competency Research is a descriptive one to find out how much the readiness of Surakarta Private University (PTS) librarians in responding to the Indonesian National Work Competency Standards (SKKNI). The survey was conducted on 46 librarians at 11 Surakarta Universities. SPSS Software with Sample T-Test is used to analyze data. From the T-Test, showed that 78.3% of librarians had not taken the Exam, 19.6% had participated in the training and 2.2% had failed the competency test. The results of this study are useful as input for leaders of the Surakarta PTS Board of Trustees in fostering and developing the library as an integral part of the Digital Ecosystem in Higher Education. For this reason, it is necessary to study the reasons for the unpreparedness of Surakarta Private University librarians in responding to Competency Test in the Digital Ecosystem.